Eksplorasi tantangan kesehatan mental dan strategi penanggulangan pada mahasiswa selama Covid-19 - Sari, Aprilina Eka (Maliki Interdisciplinary Journal, 2023)
During the COVID-19 pandemic, mental health problems spread around the world. Students experience changes in the way of life, academics, family ties, economic potential, and support networks. This article discusses mental health problems that are often faced by college students and coping mechanisms that involve social support. Students' mental health is indirectly affected by financial constraints, academic pressure, lack of learning resources, loss of self-confidence, disconnection from friends and family, over-reliance on the internet, and traumatic events. Throughout the COVID-19 epidemic, Universities have been uniformly affected. The negative impacts on mental health mentioned varied, ranging from self-harm and suicidal thoughts to worry, stress, and sadness. Family relationships and social networks have emerged as effective coping strategies for students dealing with anxiety, stress, and depression. In Indonesia, the health and welfare sector remains underfunded for mental health. Students can be helped to manage the burden of mental health that is common during a pandemic by focusing on building strong social support and leveraging strong financial subsidies, including educational resources. In order to prevent short-term and long-term adverse impacts on mental health, a national intervention strategy must be devised and implemented urgently with the assistance of multiple stakeholders, including health experts.